NDVI and SAVI as tools for monitoring changes in land use and occupation in southwestern Pará (Research, Society and Development, 2022)
Remote Sensing is a technology that allows the acquisition of information about areas or objects without maintaining physical contact. This work aimed to use passive satellite images, through vegetation cover indices, such as the Normalized Difference Vegetation Index (NVDI) and Adjusted Soil Vegetation Index (SAVI), in the years 2008 and 2018, to identify the changes undergone in 10 years of the Comunidade Linha Gaúcha community located in the municipality of Novo Progresso in the state of Pará. For this work, data from IBAMA were used, such as the spatial location of the Community and images from the United States Geological Survey (USGS) platform. for the years 2008(Landsat 5 – TM) and 2018 (Landsat 8 – OLI). Through the NDVI and SAVI method, it was possible to analyze the urban expansion around the community within a radius of 50 km, as well as observe the intense change in land use and occupation, this fact being closely linked to the presence of the Transamazon Highway, an important agent of growth in the Amazon.